The Role & Responsibility of Notaries for the Lost Minuta Due to Notary's Negligence - Arum Kurnia Sari; Jawade Hafidz (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this research is to find out and analyze: 1). The role and responsibility of the Notary in solving the problem of the loss of the minutes of the deed due to his negligence. 2) Legal implications for a Notary who due to negligence results in the loss of the minutes of the deed. The approach method in this research is sociological juridical. The data used are primary and secondary data obtained through interviews and literature study. The technique of collecting legal materials in this research is by using observation, interview and study document techniques, while the data analysis method is done by analytical descriptive method. The results of the research concluded: 1) The role and responsibility of the Notary in solving the problem of the loss of minutes of deed due to negligence is in accordance with Article 16 paragraph (1) letter b of the Notary Position Act, namely making a deed in the form of a minuta deed and storing it as part of the Notary Protocol. In resolving the loss of the minutes of the deed, one of them is to compensate the parties for losses. 2) The legal implication for a Notary who due to his negligence results in the loss of the minutes of the deed can be sanctioned, as stated in Article 9 paragraph (1) letter d of the UUJN namely temporary dismissal from his position as a Notary If the Notary in making the deed is not in accordance with the laws and regulations applicable law, in this case is not in accordance with UUJN, then the act of the Notary can be qualified as a violation of the law. Unlawful Acts are regulated in Article 1365 to Article 1380 of the Civil Code that every unlawful act causes harm to another person causing the person because of his fault to make the loss to compensate for the loss.